Policy narratives: the perlocutionary agents of political discourse. Issue 4 (1st October 2020) - Miller, Hugh T.
ABSTRACT: The ontological and epistemological footing of narrative policy research remains uncertain. In this article, interpretive approaches to policy narrative research are advanced and scientism is eschewed. Other themes in the policy narrative literature that serve as points of divergence and/or convergence include: 1) The structural features of a policy narrative; 2) The semiotic nature of policy narratives; 3) Epistemological politics; 4) Emancipatory politics within the literature; and 5) The idea that narratives are a force in themselves, that is, that narratives have agency. In addition, this article argues for a curatorial approach to redescribing policy narratives, and for an evolutionary conception of policy change and political contestation.